Radiological protection. X and gamma reference radiation for calibrating dosemeters and doserate meters and for determining their response as a function of photon energy. Calibration of area and personal dosemeters and the measurement of their response as a function of energy and angle of incidence Part 3, (22nd February 2021) - British Standards Institution,
No abstract available